Pengaruh Kecepatan Pengadukan Dan Waktu Pengendapan Menggunakan Sequencing Batch Biofilm Reactor (SBBR) Untuk Pengolahan Limbah Cair Domestik - Riri Shania; Shinta Elystia; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Greywater is a waste from kitchen, bathroom, and laundry activities that contains high organic matter. The organic matter contained in the wastewater is utilized by the microalgae Chlorella sp. as a source of nutrient and its reduce the pollutant in wastewater. This study aims to count the number cells of Chlorella sp. which grew in suspension and attached to the Kaldness 1 (K1) biocarrier media and the removal of COD in domestic wastewater using Sequencing Batch Biofilm Reactor (SBBR). The SBBR was operated on 4 cycles consisting of 30 minutes of filling time, 120 minutes of reaction, 45 minutes of decanting, and 120 minutes of stabilization time. This research was carried out with a working volume of 5 liters, 30% K1 kaldness media, and 25% suspended microalgae concentration with variations in stirring speed (40 , 60, and 80 rpm) and variation of settling time (30, 45 and 60 minutes). The best results showed a decrease in COD variations in stirring speed of 60 rpm and settling time of 60 minutes, COD removal efficiency was 78% from the initial COD concentration of 288 mg/L to 64 mg/L.Key Word : Sequencing Batch Biofilm Reactor (SBBR), Domestic Wastewater, Chlorella sp., Biocarrier Kaldness 1.